2020
DOI: 10.3390/su122410586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Types of Straw Biochar on the Mineralization of Soil Organic Carbon in Farmland

Abstract: To investigate the effects of biochar on soil carbon composition and transformation, the effects of 1%, 2%, and 5% mass ratios of banana and cassava straw biochar on carbon dioxide release, total organic carbon (TOC), soluble organic carbon (SOC), and enzyme activity in soil were studied in incubation experiments at a constant temperature in the laboratory. The results showed that the cumulative CO2 emissions from cassava straw were 15.82 (1% addition ratio) and 28.14 μg·kg−1 (2%), which were lower than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…SOC mineralization is the inevitable result of soil microbial activity. The results of this study showed that SOC mineralization after each form of straw addition showed a trend toward rapid changes in the early stages of the incubation which slowed with time, which is similar to trends observed in previous research (Hu et al, 2020). This trend was mainly related to the rapid utilization of active substrates at the beginning of the incubation period, which leads to a decrease in the availability of active substrates at the end of the incubation period (Kan et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…SOC mineralization is the inevitable result of soil microbial activity. The results of this study showed that SOC mineralization after each form of straw addition showed a trend toward rapid changes in the early stages of the incubation which slowed with time, which is similar to trends observed in previous research (Hu et al, 2020). This trend was mainly related to the rapid utilization of active substrates at the beginning of the incubation period, which leads to a decrease in the availability of active substrates at the end of the incubation period (Kan et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…These modified Terra Preta soils were characterized by 35% black carbon in the surface layer [ 4 ]. Additionally, Hu [ 5 ] proposed that the mineralization of soil organic carbon (SOC) showed a strong negative excitation effect following the biochar addition, which reduced the mineralization rate of the SOC. Song [ 6 ] also indicated that the addition of biochar could increase the content of the SOC, which could be used by microorganisms, thus inhibiting organic carbon mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Soil cation exchange capacity (CEC) was determined by the barium chloride-sulfuric acid forced exchange method (Zhang et al, 2010). Soil organic carbon (SOC) was determined by the potassium dichromate oxidation-spectrophotometric method (Hu et al, 2020). Soil dissolved organic carbon (DOC) content was determined by TOC total organic carbon analyzer (Huang et al, 2018).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…where V 0 is the volume of standard hydrochloric acid consumed during the blank titration, V is the volume of standard hydrochloric acid consumed during the sample titration, c is the concentration of standard hydrochloric acid, 0.022 is the molar mass of carbon dioxide (1/2CO 2 ), M (1/2CO 2 ) = 0.022 g mmol −1 , 22.4 × 1000/44 is the number of milliliters per gram of CO 2 in the standard state; △t is the incubation interval (d); C t is the cumulative mineralization at incubation time t (d), C 0 is the potential mineralization of soil carbon, C (mg•kg −1 ); k is the rate constant of soil carbon mineralization, d −1 ; t is the incubation time, day (d) (Hu et al, 2020).…”
Section: Cumulative Mineralization Comentioning
confidence: 99%